Development of STEM-Based Physics E-Module with Self-Regulated Learning to Train Students’ Creative Thinking Skills - Dwi Ayu Lestari; Suwarma, Irma Rahma; Suhendi, Endi (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
Twenty-first century skills are recognized as a competency standard that students need to possess to support the demands of success both in work and in life in the future, especially in learning. In line with this, learning that can accommodate 21st-century skills is learning that has a balance between the scientific approach and the use of technology. One of the efforts that can be made is to develop teaching materials in the form of electronic modules that integrate Science, Technology, Engineering, and Mathematics (STEM) to train creative thinking skills that are also adjusted to the applicable school curriculum. However, most of the teaching materials, especially the modules that are used in general, are only printed modules. Based on these problems, we need electronic modules (e-modules) that direct students to have 21st-century skills and the dimensions that exist in the independent learning curriculum. This study aims to develop an e-module based on STEM and self-regulated learning about global warming topics to train students’ creative thinking skills. This type of research involves adapting a 4-D development model. Which consist of defining, designing, developing, and disseminating. The data were gathered through questionnaires and tests. The questionnaire instrument consists of an expert validation questionnaire of three experts. Meanwhile, the test instrument consisted of a pre-test and a post-test, which were tested on 32 students in class X majoring in science. The N-gain score for creative thinking skills is 0.60 in the medium category. Based on the results of this study, the development of a STEM-based physics e-module with self-regulated learning on the global warming topic can train students' creative thinking skills.